2019
DOI: 10.1098/rsos.180667
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and synthetic particles ingested by deep-sea amphipods in six of the deepest marine ecosystems on Earth

Abstract: While there is now an established recognition of microplastic pollution in the oceans, and the detrimental effects this may have on marine animals, the ocean depth at which such contamination is ingested by organisms has still not been established. Here, we detect the presence of ingested microplastics in the hindguts of Lysianassoidea amphipod populations, in six deep ocean trenches from around the Pacific Rim (Japan, Izu-Bonin, Mariana, Kermadec, New Hebrides and the Peru-Chile trenches), at depths ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(147 citation statements)
references
References 66 publications
(114 reference statements)
4
132
1
10
Order By: Relevance
“…This is being remedied as the research field matures. Microplastics have recently been discovered in presumably pristine locales, including Arctic sea ice (Peeken et al, ), the Antarctic (Waller et al, ), remote mountain ranges (Allen et al, ), and deep ocean trenches (Jamieson et al, ). As is common with emerging environmental issues, much early work focused on describing the extent of microplastic contamination, although sampling and analytical methods are not yet up to the challenge.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is being remedied as the research field matures. Microplastics have recently been discovered in presumably pristine locales, including Arctic sea ice (Peeken et al, ), the Antarctic (Waller et al, ), remote mountain ranges (Allen et al, ), and deep ocean trenches (Jamieson et al, ). As is common with emerging environmental issues, much early work focused on describing the extent of microplastic contamination, although sampling and analytical methods are not yet up to the challenge.…”
Section: Overviewmentioning
confidence: 99%
“…Avery‐Gomm et al () observed that 79% of sea bird (northern fulmar, Fulmarus glacialis ) samples collected from the southeastern Canadian waters of the Labrador Sea contained microplastics in their digestive tracts. Remarkably, Jamieson et al () recovered mainly microfibers from 72% of the Lysianassoidea amphipods sampled at 7,000 to 10,890 m in six of the deepest ocean trenches in the Pacific Rim. In freshwater environments, a recent study found that 50% of riverine macroinvertebrates (including detritivores and filter feeders) contained microplastics (Windsor et al, ).…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%
“…It has been estimated that between 1950 and 2015 at least 8,300,000,000 tons of plastic -29 times the weight of all adult humans on Earth (Walpole et al, 2012) -has been produced, and that over half of this has by now been discarded as waste (Geyer, Jambeck, & Law, 2017). Given the high durability of plastic, most of this plastic waste is still present in the environment, and some is even found in remote places such as the Antarctic (Barnes, Galgani, Thompson, & Barlaz, 2009) and in the Mariana Trench (Jamieson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…44 The results are in accord with another recent study, which showed that microplastics and other synthetic particles were being ingested by amphipods (small crustaceans), in six of the deepest parts of the world's oceans. 45 High concentrations of persistent organic pollutants (POP) have also been measured in the bodies of amphipods that live in the Mariana and Kermadec trenches (both >10 km deep). Since the levels were far higher than those measured in neighbouring areas where heavy industry operates, it appears that the amphipods are bioaccumulating these anthropogenic pollutants, which are pervasive across the world's oceans and to full ocean depth.…”
Section: Missing Plastics?mentioning
confidence: 99%